Measuring success in IVF is a complex multidisciplinary task: time for a consensus?. Issue 5 (November 2021) - Rienzi, Laura; Cimadomo, Danilo; Vaiarelli, Alberto; Gennarelli, Gianluca; Holte, Jan; Livi, Claudia; Aura Masip, Monica; Uher, Petr; Fabozzi, Gemma; Ubaldi, Filippo Maria
Abstract: The goal of an IVF cycle is the birth of at least one baby per intention to treat. However, IVF cannot confer competence on an embryo, but only can provide each couple with a safe treatment to meet a predetermined chance of success. This commentary highlights how clinical, financial and patient-centred perspectives should be included in the definition of success in IVF. The primary outcome, which is the cumulative live birth delivery rate per intention to treat, must always be complemented by analyses of risks, costs and time invested, as well as by measures of patient satisfaction. Finally, it is essential, whenever clinical conditions exist, to limit treatment discontinuation after failed attempts. Constant monitoring of the data is pivotal and must be adjusted for patient characteristics and compared with national and international registers. The authors aimed to review all these aspects and highlight the points that are still open for discussion. Is it time for a consensus?